Immune and biochemical responses in skin differ between bovine hosts genetically susceptible and resistant to the cattle tick Rhipicephalus microplus. Issue 1 (December 2017) - Franzin, Alessandra; Maruyama, Sandra; Garcia, Gustavo; Oliveira, Rosane; Ribeiro, José; Bishop, Richard; Maia, Antônio; Moré, Daniela; Ferreira, Beatriz; Santos, Isabel
Abstract Background Ticks attach to and penetrate their hosts' skin and inactivate multiple components of host responses in order to acquire a blood meal. Infestation loads with the cattle tick, Rhipicephalus microplus, are heritable: some breeds carry high loads of reproductively successful ticks, whereas in others, few ticks feed and reproduce efficiently. Methods In order to elucidate the mechanisms that result in the different outcomes of infestations with cattle ticks, we examined global gene expression and inflammation induced by tick bites in skins from one resistant and one susceptible breed of cattle that underwent primary infestations with larvae and nymphs ofR. microplus . We also examined the expression profiles of genes encoding secreted tick proteins that mediate parasitism in larvae and nymphs feeding on these breeds. Results Functional analyses of differentially expressed genes in the skin suggest that allergic contact-like dermatitis develops with ensuing production of IL-6, CXCL-8 and CCL-2 and is sustained by HMGB1, ISG15 and PKR, leading to expression of pro-inflammatory chemokines and cytokines that recruit granulocytes and T lymphocytes. Importantly, this response is delayed in susceptible hosts. Histopathological analyses of infested skins showed inflammatory reactions surrounding tick cement cones that enable attachment in both breeds, but in genetically tick-resistant bovines they destabilized the cone. The transcription data provided insights into tick-mediated activation of basophils, which have previously been shown to be a key to host resistance in model systems. Skin from tick-susceptible bovines expressed more transcripts encoding enzymes that detoxify tissues. Interestingly, these enzymes also produce volatile odoriferous compounds and, accordingly, skin rubbings from tick-susceptible bovines attracted significantly more tick larvae than rubbings from resistant hosts. Moreover, transcripts encoding secreted modulatory molecules by the tick were significantly more abundant in larval and in nymphal salivary glands from ticks feeding on susceptible bovines. Conclusions Compared with tick-susceptible hosts, genes encoding enzymes producing volatile compounds exhibit significantly lower expression in resistant hosts, which may render them less attractive to larvae; resistant hosts expose ticks to an earlier inflammatory response, which in ticks is associated with significantly lower expression of genes encoding salivary proteins that suppress host immunity, inflammation and coagulation.